Analysis of Chemical Components and Antioxidant Activity in Nutmeg Shell Liquid Smoke Processed through Rotary Evaporator Purification - Watuseke, Rommy David; Gugule, Sanusi; Lombok, Johny Z (Indonesian Journal of Chemical Research, 2024)
This study aims to analyze liquid smoke's chemical content and antioxidant activity from pyrolysis of nutmeg (Myristica fragrans) shell with rotary evaporator purification. A rotary evaporator purified liquid smoke from the pyrolysis of nutmeg shells. Identification of the chemical components of liquid smoke from the pyrolysis of nutmeg shells was carried out by Gas Chromatography-Mass Spectroscopy (GC-MS), and Antioxidants were measured using the DPPH (2,2-diphenyl-1-picrylhydrazyl) method with absorbance at a wavelength of λ 517 nm. The results of GC-MS analysis showed 14 peaks and 19 types of compounds detected with the 2-methylphenol compound component located at a retention time of 4.974 minutes, standing out with the largest contribution in terms of area, reaching 47.74%. The antioxidant test showed that the nutmeg shell has IC50 values before and after rotary evaporation of 0.40% and 0.07%, having strong antioxidant activity, and the results at a concentration of 3.2 mg/ml provided a level of free radical protection of more than 50%, namely 91.14%. The main compounds that play as antioxidants are phenol compounds and their derivatives, such as 2-methoxy-phenol and 2-methoxy-4-methyl-phenol.